2021
DOI: 10.1037/lhb0000449
|View full text |Cite
|
Sign up to set email alerts
|

Race, witness credibility, and jury deliberation in a simulated drug trafficking trial.

Abstract: Objective: The present study integrates several distinct lines of jury decision-making research by examining how the racial identities of the defendant and an informant witness interact in a federal drug conspiracy trial scenario and by assessing whether jurors' individual racial identity and jury group racial composition influence their judgments. Hypotheses: We predicted that jurors would be biased against the Black defendant and would be more likely to convict after exposure to a White informant, among othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
(150 reference statements)
0
11
2
Order By: Relevance
“…White jurors were more likely than Black jurors to find the defendant not guiltysuggesting that regardless of defendant race, White jurors were more lenient. Importantly, this finding is counter to prior research finding Black jurors more lenient than White jurors (Fitzgerald & Ellsworth, 1984;Foley & Chamblin, 1982;Shaw et al, 2021;Sommers & Ellsworth, 2000). However, in the context of the OJ Simpson trial, White jurors viewed defendants of an elevated status (celebrity/athlete) more favorably than Black jurors (Skolnick & Shaw, 1997).…”
Section: Study 2 Discussioncontrasting
confidence: 81%
“…White jurors were more likely than Black jurors to find the defendant not guiltysuggesting that regardless of defendant race, White jurors were more lenient. Importantly, this finding is counter to prior research finding Black jurors more lenient than White jurors (Fitzgerald & Ellsworth, 1984;Foley & Chamblin, 1982;Shaw et al, 2021;Sommers & Ellsworth, 2000). However, in the context of the OJ Simpson trial, White jurors viewed defendants of an elevated status (celebrity/athlete) more favorably than Black jurors (Skolnick & Shaw, 1997).…”
Section: Study 2 Discussioncontrasting
confidence: 81%
“…While the findings speak to our theoretical understanding of bias, including in small group contexts such as juries, there is also more work to be done on how individuals' attributes and experiences contribute to the group‐level process. Prior research indicates that jurors subjectively experience the deliberation process differently as a function of “status characteristics” such as gender and racial identity (Winter & Clair, 2018) and that decision‐making processes and outcomes vary considerably as a function of jury diversity (Shaw et al, 2021; Sommers, 2006). While we preliminarily examined how juror race impacted verdict outcomes in this study, further research on the racial and gender dynamics of deliberation and decision making is warranted, including whether these instructions may improve the subjective experience for jurors from marginalized groups.…”
Section: Discussionmentioning
confidence: 99%
“…While federal criminal juries are composed of 12 individuals, the smaller juries allowed for a sufficient number of jury units to meaningfully analyze, while not sacrificing a group decision‐making process. This approach has been successfully used in multiple prior experimental jury decision‐making studies (e.g., Lynch & Haney, 2009; MacCoun & Kerr, 1988; Peter‐Hagene, 2019; Sommers, 2006; Shaw et al, 2021). Data from three groups, totaling 16 participants, were removed from the analyses: two were removed due to technical difficulties during data collection, rendering the data unreliable, and one was removed due to the dismissal of a participant for disruptive behavior, resulting in too few participants remaining to comprise a jury unit of at least four people.…”
Section: The Studymentioning
confidence: 99%
“…Additionally, defendant and eyewitness race have been found to influence jurors' perceptions of defendant and eyewitness credibility (Kurinec & Weaver, 2019;Saulnier et al, 2020;Shaw et al, 2021). Saulnier et al's (2020) explored the effect of eyewitness race (Black or White) and body-worn cameras on verdicts and defendant credibility.…”
Section: Defendant Race and Juror Decisionsmentioning
confidence: 99%
“…Defendants supported by White eyewitnesses were less likely to be found guilty and were viewed as more credible than defendants supported by Black eyewitnesses. Shaw et al (2021) investigated eyewitness credibility in a federal narcotics trial. They found that eyewitnesses who supported White defendants were viewed as more credible than eyewitnesses that supported Black defendants.…”
Section: Defendant Race and Juror Decisionsmentioning
confidence: 99%